PEMETAAN POTENSI BENCANA LONGSOR DI KELURAHAN KEMBANG ARUM - Widjonarko Widjonarko; Holi Bina Wijaya (Department of Urban and Regional Planning, Diponegoro University, 2014)
Disaster is a real fact that sometimes less attention by both government and society. This is reflected from the hustle bustle of activity that occurs after the disaster compared with efforts to minimize the impact of disasters. Coexist with a culture of disaster has not become either by the government or the public. One push to institutionalize a culture coexist with disaster is to drive the community to better identify more closely the potential disaster and to encourage people to be able to map out the potential disaster in the environment around them.Kembang Arum Society in general does not fully know and understand the potential and landslide conditions in their neighborhood. The Community knew after the collapse of the cliff retaining embankments. People were not so attentive to cutting hills activities in surround them. This research resulted the map of lanslide situation. basedon that, the society of Kembang Arum will be know that the existing condition will change in high risk of landslides in the long term,especially in areas with hills and steep slopes.